PNES around the world: Where we are now and how we can close the diagnosis and treatment gaps—an ILAE PNES Task Force report. Issue 3 (23rd June 2017) - Kanemoto, Kousuke; LaFrance, W. Curt; Duncan, Roderick; Gigineishvili, David; Park, Sung‐Pa; Tadokoro, Yukari; Ikeda, Hiroko; Paul, Ravi; Zhou, Dong; Taniguchi, Go; Kerr, Mike; Oshima, Tomohiro; et al.
Summary: An international consensus clinical practice statement issued in 2011 ranked psychogenic nonepileptic seizures (PNES) among the top three neuropsychiatric problems. An ILAE PNES Task Force was founded and initially charged with summarizing the current state of the art in terms of diagnosis and treatment, resulting in two publications. The first described different levels of diagnostic certainty. The second summarized current knowledge of management approaches. The present paper summarizes an international workshop of the ILAE PNES Task Force that focused on the current understanding and management of PNES around the world. We initially provide a knowledge update about the etiology, epidemiology, and prognosis of PNES—in adults and in special patient groups, such as children, older adults, and those with intellectual disability. We then explore clinical management pathways and obstacles to optimal care for this disorder around the world by focusing on a number of countries with different cultural backgrounds and at very different stages of social and economic development (United Kingdom, U.S.A., Zambia, Georgia, China, and Japan). Although evidence‐based methods for the diagnosis and treatment of PNES have now been described, and much is known about the biopsychosocial underpinnings of this disorder, this paper describes gaps in care (not only in less developed countries) that result in patients with PNES not having adequate access to healthcare provisions. A range of challenges requiring solutions tailored to different healthcare systems emerges. Continued attention to PNES by the ILAE and other national and international neurologic, psychiatric, and health organizations, along with ongoing international collaboration, should ensure that patients with PNES do not lose out as healthcare services evolve around the world.